THE PROBLEM OF ACTIVIZATION OF ECONOMY INNOVATIVE DEVELOPMENT - T. Nikolenko (Вестник университета)
The problems of activation of innovative development of the country’s economy have been considered, the main objects of which are high-tech enterprises. The current state of the process of introduction of innovative products in Russia has been assessed and the role of high-tech enterprises in the rise of the national economy has been revealed. In the article the direct connection of innovative development from the effective implementation of investment programs, which correspond to the specific features of high-tech enterprises has been revealed. In addition, the necessity of drawing up a program for the development of new products has been substantiated, which should contain an assessment of the competitive position of the enterprise in the market, an analysis of internal capacity and verification of the current capabilities of the organization to the conditions of transition to the production of innovative products.